"Illiberal Spaces:" Uzbekistan's extraterritorial security practices and the spatial politics of contemporary authoritarianism. Issue 1 (20th November 2018) - Lewis, David
Abstract : Research on comparative authoritarianism has tended to neglect spatial approaches to the politics of non-democratic states. This article argues that spatial theory offers a useful framework for exploring extraterritorial security practices designed to counter political opposition among migrant and exile communities. A case study of Uzbekistan explores how the state responded to the perceived security threats posed by rapidly growing communities of labor migrants and the activities of many political and religious activists in exile. The security services developed a network of extraterritorial intelligence and security mechanisms – including surveillance, detention, interrogation and forced returns – to pre-empt or respond to any perceived threats to the regime emanating from abroad. These security practices extended the state in complex ways beyond its borders, resulting in new "state spaces" that reproduced elements of domestic repression in other jurisdictions. The article suggests that such extraterritorial practices are typical of contemporary authoritarian regimes, as such states seek to manage the spatial challenges produced by mass global migration, international financial flows, and transnational processes of knowledge production.